The nature of meaning in the age of Google. Google, Indexing, Web, Meaning - Terrence A. Brooks (Information Research: An International Electronic Journal)
The culture of lay indexing has been created by the aggregation strategy employed by web search engines such as Google. Meaning is constructed in this culture by harvesting semantic content from web pages and using hyperlinks as a plebiscite for the most important web pages. The characteristic tension of the culture of lay indexing is between genuine information and spam. Google's success requires maintaining the secrecy of its parsing algorithm despite the efforts of web authors to gain advantage over the Googlebot. Legacy methods of asserting meaning such as the META keywords tag and Dublin Core are inappropriate in the lawless meaning space of the open Web. A writing guide is urged as a necessary aid for web authors who must balance enhancing expression versus the use of technologies that limit the aggregation of their work.